The Antecedent of Customer Satisfaction and Its Impact on Customer Retention in Tourism as Hospitality Industry - Putra Barusman et al., Andala Rama (International Journal of Advanced Science and Technology, 2019)
Taking a case study of tourism as hospitality industry in Lampung Province in Indonesia, we analyze the antecedent of customer satisfaction and its impact on customer retention. Using Structural Equation Model (SEM), we find that customer relationship management has a significant impact on service quality, customer satisfaction and customer retention. Moreover, the impact of service quality on customer satisfaction and the one of customer satisfaction on customer retention are aslo significant. Relying on the findings, we recommend some strategies for the government of Lampung Province, e.g. training local people to behave more friendly in welcoming domestic or international tourists, fixing all lodging facilities, creating more souvenirs with Lampung’s ornaments and developing management system adopting global changes in technology, communication and trend.